Using Mathematical Models within the Cosmetological Aid Organization in the Context of Botulinum Toxin Therapy of Upper Face Skin Age-Related Changes - Olga Nikolaevna Krasilnikova (Journal of Global Pharma Technology, 2016)
Mathematical modeling is the language of modern science. This paper describes the application of the mathematical evaluation of the clinical efficiency of botulinum toxin therapy of age-related changes in the skin of the upper half of the face on the example of correcting the three zones of the patient. For this purpose, we used the scoring scale; schedules that help the doctor get new information about the effectiveness and quality of the procedure throughout the observation period, and master practical skills of quality examination. Such an approach in cosmetology will make it closer to evidence-based medicine, contributing to the objectification and systematization of the accumulated data.Keywords: Cosmetological care, Botulinum toxin therapy, Evaluation of the efficiency of injection correction of age-related facial skin changes, Quality of medical care, Integral quality factor.